Architectonic, architect Ivan Antić: on the occasion of the 100th anniversary of birth / Dijana Milašinović Marić and Igor Marić - Manić, Božidar J. (Arhitektura i urbanizam, 2025)
The monograph Architectonic, architect Ivan Antić: on the occasion of the 100th anniversary of birth, by the authors Prof. Dr. Dijana Milašinović Marić, art historian, and Dr. Igor Marić, architect, Principal Research Fellow, was published at the end of 2023. The work and life of academician Professor Ivan Antić, architect, one of the most significant creators of Serbian architecture of the second half of the 20th century, are comprehensively presented on 235 pages of the text equipped with scientific apparatus, with accompanying illustrations. The authors received the Ranko Radović Award for this publication in 2024 in the category of critical theoretical texts on architecture, urbanism and the city.